Salivary α-Amylase and Albumin Levels in Patients with Chronic Periodontitis and Poorly or Well Controlled Type II Diabetes Mellitus - Ahmed, Maha A (Journal of Baghdad College of Dentistry, 2016)
Background: Recent studies suggest that chronic periodontitis (CP) and type2 diabetes mellitus (T2DM) are bidirectionally associated. Analysis of saliva as a mirror of oral and systemic health could allow identification of α amylase (α-Am) and albumin (A1) antioxidant system markers to assist in the diagnosis and monitoring of both diseases. The present study aims at comparing the clinical periodontal parameters in chronic periodontitis patients with poorly or well controlled Type 2Diabetes Mellitus, salivary α-Am, A1, flow rate (FR) and pH then correlate between biochemical, physical and clinical periodontal parameters of each study and control groups. Materials and Methods: 80 males, with an age range of (35-50) years were divided into four groups, (20 subjects each): two groups had well or poorly controlled Type 2Diabetes Mellitus both of them with chronic periodontitis, group of patients with only chronic periodontitis and control group with healthy periodontium and systemically healthy. From all subjects unstimulated whole salivary samples were collected to measure FR, pH, Al and α – Am, then clinical periodontal parameters (plaque index, gingival index, bleeding on probing, probing pocket depth and clinical attachment level)were recorded. Results: Patients had chronic periodontitis with poorly controlled Type 2Diabetes Mellitus demonstrated the highest median values of all clinical periodontal parameters and highest increase in levels of salivary α-Am and Al with lowest median values of FR and pH, in addition to the highly significant differences among the study and control groups regarding biochemical and physical parameters. Positive correlations were revealed between α-Am with Al and both of them with all clinical periodontal parameters but, they were negative with FR and pH. Conclusion: Patients with poor glycemic control had more severe periodontal tissue break down with decrease in FR and pH also obvious increase in levels of A1 and α- Am so, these biochemical markers will provide an objective phenotype to allow practitioners for early diagnosis, which is essential for improved prognosis and effective delay of clinical complications associated with chronic periodontitis and DM and an important strategy to lower the incidence of both diseases world wide. Keywords: Periodontitis, Type 2Diabetes Mellitus, salivary albumin and α-amylase.